Peningkatan Kesiapsiagaan Kader PKK Cibiru Wetan untuk Ketahanan Bencana di Masa Pandemi COVID-19 - Nur Intan Hayati Husnul Khotimah; Fauzan Zein Mutaqin; Soni Muhsinin; Widhya Aligita; Eki Pratidina; Iceu Mulyati; Yulianti Anjayani; Untung Sudharmono; Etika Emaliyawati; Ellin Febrina; Aiyi Asnawi (Jurnal Pengabdian Pada Masyarakat, 2022)
IMPROVİNG THE PREPAREDNESS OF CİBİRU WETAN PKK CADRES FOR DİSASTER RESİLİENCE DURİNG THE COVİD-19 PANDEMİC. Cibiru is a high-risk area for natural and man-made disasters, so efforts must be made to reduce the risk of disaster impacts. One effort that can be made is to strengthen the Cibiru Wetan village's resilience by increasing preparedness to deal with emergency cases caused by disasters, such as cases of respiratory arrest, cardiac arrest, trauma, and respiratory emergencies caused by COVID-19. Community service is performed to improve the preparedness of Cibiru Wetan PKK cadres for disaster-resilient village resilience during the COVID-19 Pandemic. The method of implementing community service by simulating basic life support, trauma event handling, prevention and handling of COVID-19 emergencies, and the production of health drinks made from natural ingredients such as ginger, honey, lime, cardamom, and turmeric to boost immunity. As a result, the Cibiru Wetan PKK cadres were able to simulate basic life support, first aid in the event of trauma, and respiratory disorders caused by COVID-19, as well as process natural ingredients into healthy drinks to increase immunity, thereby increasing the Cibiru Wetan village's resilience.